Emotional competence, behavioural patterning, and executive functions. Issue 10 (24th August 2019) - Mohtasham, Mandana K.; Patterson, Allyson B.; Vennergrund, Katherine C.; Chen, Eileen; Pasnak, Robert
ABSTRACT: The importance of social-emotional competence, executive functioning, and behavioural recognition of patterns by young children is receiving increased attention from researchers, schools, parents, and teachers due to the beneficial outcomes of children who have skills in each. This paper presents studies of the correlations between these variables in the fall and again in the spring of a preschool year, and culminates in a time-lagged comparison of the relationships between these skills during one preschool year. The most clear-cut findings were (1) that there is a successive, but not simultaneous, relation between emotional development and behavioural patterning, and (2) that the ability to inhibit natural responses is a forerunner to emotional development.